2001
DOI: 10.1055/s-2001-919048
|View full text |Cite
|
Sign up to set email alerts
|

Drugs in liver disease and during albumin dialysis -MARS

Abstract: In liver diseases the pharmacokinetics and pharmacodynamics of drugs may be changed to a different degree. At present, there is no satisfactory test for the quantitative determination of metabolic liver function. Child-Pugh scoring is a poor predictor of drug-metabolising capacity. In patients with liver disease the grade of reduction of the metabolic capacity (dependent on hepatic blood flow and enzyme activity) and of plasma protein binding rate as well as the influence of extrahepatic elimination is difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…Since there is a high risk of invasive fungal infections in liver failure, antifungal therapy is frequently required in this group of patients. In contrast to observations on pharmacokinetics of antibiotics during artificial liver support, for example, levofloxacin, ceftriaxone, teicoplanin, and ceftazidime (8,20), the removal of lipid-formulated AMB appears to be only moderately enhanced by AD. Furthermore, this effect may be compensated by the delayed elimination due to liver failure in this group of patients.…”
Section: Resultscontrasting
confidence: 79%
“…Since there is a high risk of invasive fungal infections in liver failure, antifungal therapy is frequently required in this group of patients. In contrast to observations on pharmacokinetics of antibiotics during artificial liver support, for example, levofloxacin, ceftriaxone, teicoplanin, and ceftazidime (8,20), the removal of lipid-formulated AMB appears to be only moderately enhanced by AD. Furthermore, this effect may be compensated by the delayed elimination due to liver failure in this group of patients.…”
Section: Resultscontrasting
confidence: 79%
“…An in vitro study revealed that the elimination of highly protein‐bound drugs, such as TP, is significantly higher with AD compared to continuous veno‐venous hemodialysis. A reduction of TP levels by 90% was found within 6 h during AD (14). Bacterial killing by TP depends on the time above the minimal inhibitory concentration.…”
Section: Resultsmentioning
confidence: 93%
“…This might result in subtherapeutic concentrations. Pharmacokinetic data on antimicrobial agents administered under AD are very sparse (13–16). Therefore, we assessed TP pharmacokinetics in a critically ill patient requiring AD.…”
mentioning
confidence: 99%
“…However, our approach allows a breakdown of the various components of the MARS circuit to antibiotic elimination. Unlike previous reports, our results indicate that also low albumin‐bound drugs like meropenem may be removed by MARS and dose adjustment is mandatory …”
Section: Discussionmentioning
confidence: 98%
“…So far, very little data about antibiotic clearance by the MARS system exist; they cover mainly the highly albumin‐bound glycopeptide teicoplanin, but not substances like the low albumin‐bound meropenem and the moderately albumin‐bound moxifloxacin …”
mentioning
confidence: 99%